IMPROVING STUDENTS’ READING COMPREHENSION ON ROMANCE NARRATIVE TEXT BY USING JIGSAW - Atika Khairunisa; Eni Rosnija; Yanti Sri Rezeki (Universitas Tanjungpura, 2019)
AbstractThis research proposed to improve students’ reading comprehension on romance narrative text by using jigsaw in which the subject was students of the eleventh grade of MAS Darul Ulum Kubu Raya in Academic Year 2018/2019. This research was conducted based on the problems found in the classroom. First, students could not comprehend the specific information from the text. Second, students were not able to identify the generic structure of the text. Third, the students learned to be passive during the teaching and learning activities. This research was conducted through a Classroom Action Research in two cycles, each cycle consisted of six stages, they were problem statement, data collection, analysis and feedback, action planning, taking action, and evaluation and follow-up. The participants of this research were the English teacher and 25 students in class eleven. The writer used observation checklist, field notes and assessments to collect the data. The writer elaborated the result of observation checklist, field notes, and students’ assessment to get the research findings.In the first cycle, the students’ mean score was 65.4 and it increased into 72.8 in the second cycle. Base on the research findings, Jigsaw could improve students’ reading comprehension on romance narrative text. Keywords: Improve, Jigsaw, Narrative Text, Reading Students.